Accountability For Financial Management Based On Isak 35 On The Financial Reports Of Non-Profit Organizations For Prosperity (Case Study At The Taqwa Muhammadiyah Mosque Kp. Dadap City Of Medan) - Rezeki, Sri; Harmain, Hendra; Tambunan, Khairina (Universitas Dehasen Bengkulu, 2023)
This study aims to determine the problem of recording the financial statements of the Taqwa Muhammadiyah Mosque which are still simple and not in accordance with the applicable Financial Accounting Standards Interpretation, namely ISAK 35. The purpose of this research is to examine the prosperity of the mosque and aims to find out how ISAK 35 is implemented at the Taqwa Mosque. Muhammad Kp. City of Medan. The type of research that the authors use is field research with qualitative methods. The technique used is in the form of documentation and interview techniques, namely the data contained in the financial reports of the Taqwa Muhammadiyah Mosque for the period of January 2023 which were compiled by the management of the Taqwa Muhammadiyah mosque. The results of the research show that the recording of financial reports carried out by the Taqwa Muhammadiyah Mosque has 5 components, namely a report on financial position of Rp. 22,178,500 while the comprehensive income report is Rp. 3,786,000, Report on changes in net assets of Rp. 22,178,500, the cash flow statement amounted to Rp. 22,178,500, and notes to the financial statements. And the mosque has been said to be prosperous because apart from the infaq box, the mosque's income is also in the distribution of building rent.